Integrative Communication Model in Handling Stunting: A Case Study in Bantaeng Regency - Yanti, Sri Dewi; Unde, Andi Alimuddin; Sultan, M Iqbal; Akbar, Muh. (Journal of Public Representative and Society Provision, 2025)
Stunting remains a critical health issue in Indonesia, with long-term impacts on human capital and economic development. It is caused by chronic malnutrition, resulting in impaired physical and cognitive growth. This study examines the implementation of an integrative communication model for addressing stunting in Bantaeng, South Sulawesi, using a qualitative case study approach. The research aims to explore how communication strategies are applied across sectors to reduce stunting and improve public health outcomes. Data was collected through field observations and interviews with key stakeholders, including government agencies, health workers, and community leaders. Findings indicate that the success of the program relies on structured inter-sectoral coordination, accurate and integrated data, and the active participation of local communities. The study highlights the importance of using local values, such as language and food traditions, to strengthen communication and increase community engagement. The integrative communication model in Bantaeng combines vertical and horizontal communication, ensuring coordinated actions among stakeholders. The ideal model emphasizes cross-sector communication, community participation, accurate data usage, and deliberative communication practices. This research provides insights into the effectiveness of communication in stunting prevention and offers recommendations for enhancing inter-sectoral collaboration and local participation. The model developed in Bantaeng could serve as a reference for similar health communication programs in Indonesia.